Management of Hyperkalemia in Patients with Acute Kidney Injury Post Septic Shock: A Case Report - Sutisnu, Ajeng Andini; Emaliyawati, Etika; Anna, Anastasia (Padjadjaran Acute Care Nursing Journal, 2025)
Introduction: Hyperkalemia often occurs in patients with acute kidney injury due to decreased ability to excrete potassium. This case report aims to describe treating hyperkalemia in patients with acute kidney injury (AKI) after septic shock. Method: Case reports detailed the management of hyperkalemia correction using a combination of insulin with 40% Dextrose solution, Ca Gluconate, and hemodialysis therapy. Results: A 64-year-old male patient was admitted to the GICU due to septic shock and AKI after undergoing surgery to extract the 36th and 38th teeth accompanied by a retropharyngeal abscess. The physical examination results showed palpitations, tachycardia, hypertension, and grade 1 pitting edema in the upper extremities. The laboratory checks showed hyperkalemia, and an ECG showed sinus tachycardia. The nurse carried out collaborative therapy for potassium correction using a combination of 10-unit insulin and 40% Dextrose, as much as 2 flacons, and Ca Gluconate. Conclusion: Correction of hyperkalemia used a combination of 10-unit insulin and D40%, and Ca Gluconate therapy was the most widely used intervention because it had a rapid onset and hypokalemic effect. Unfortunately, this therapy could not overcome refractory hyperkalemia in these cases, so the patient was advised to undergo hemodialysis therapy.